Implementing Pillar Two: Challenges and Opportunities in the Global Minimum Tax Framework - Fadilah, Resmi Afifah (Indonesian Scientific Publication, 2024)
This study provides a narrative review of the Global Minimum Tax (GMT) under the OECD/G20 Pillar Two framework, assessing its effectiveness in reducing corporate tax avoidance and addressing harmful tax competition. The review draws on peer-reviewed literature collected through Scopus and Web of Science, using targeted keywords such as Global Minimum Tax, Pillar Two, Base Erosion and Profit Shifting, and international taxation. Inclusion criteria focused on studies examining policy impacts, compliance outcomes, and comparative evidence across jurisdictions. Results indicate that the GMT has improved compliance and tax revenue in advanced economies with robust institutions, where an average increase of 8% in tax revenue was reported after implementation. However, in developing countries, weak administrative capacity and reliance on tax-based investment strategies hinder effective adoption, raising concerns about deepening global inequalities. The discussion emphasizes systemic factors—including institutional infrastructure, policy divergence, and socio-economic conditions—that mediate implementation outcomes. It also highlights the importance of international cooperation, coordinated regional directives, and policy innovations that align fiscal measures with sustainable development objectives. Limitations in the existing literature, particularly reliance on model-based projections and insufficient empirical evidence from developing regions, point to the need for future research using mixed methods and longitudinal approaches. The findings underscore that while the GMT represents a landmark step in international taxation, its success depends on enhancing administrative capacity, promoting policy harmonization, and embedding equity into global tax governance.